Effect Of Ginger Base Extract (Zingiber Officinale Var Rosc) On Medical Speed Of White Rats (Rattus Novergicus) - Erwien isparnadi; Fatah Jati Pamungkas; Diah Hermayanti; Yoyok Subagio (Saintika Medika : Jurnal Ilmu Kesehatan dan Kedokteran Keluarga, 2022)
When the skin is scratched by rubbing it on a rough surface, ginger contains anti-inflammatory compounds that help accelerate the healing of scratches. The therapeutic effect of elephant ginger extract (Ginger Officinale Var Rosc) on white male rats (Rattus norvegicus) Wistar strain? The only real test was an experiment with a control group design. This study was conducted for seven days with samples divided into four groups, namely P1 (NaCl 0.9%), P2 (Gel 0%), P3 (Ginger Agar 8%), and P4 (Ginger Agar 12%). The gel extract application was observed on the 1st, third and fifth days. On the seventh day, it was analyzed by the One Way ANOVA test. The results of the average exfoliated wound area on day 7 P1 = 1.47 cm2, P2 = 0.58 cm2, P3 = 0.31 cm2, P4 = 0 cm2, the average healing rate P1 = 4.9%/day, P2 = 10.6%/day, P3 = 12.31 performances. %/day, P4 = 14.2%/day. The results of the one-way ANOVA test showed a significant effect (p < 0.05). Elephant ginger extract gel (Zingiber officinale var rosc) can accelerate the healing of abrasions in white rats (Rattus norvegicus).